A importância intrínseca e a confiabilidade dos escólios de Acarnenses - Moura Filho, Lauro Inácio de (2018)
The scholia on the Acharnians are the object of analysis of this dissertation, which places itself in a position opposite to those who see the scholia only as a paratext – on to use a concept of Genette (2010) – or as an adjunct to the text with which they were copied. The your objective is firstly to demonstrate that the scholia, whether on the Acharnians or on any other, have an expressive intrinsic importance, and can be taken as an object of research, independently of the work they comment on. The research showed four aspects of the scholia that defend this point of view: as a lexicographical contribution, as testimony of fragments of lost works, as substrate of a section of Aristophanes’ Colometry and as a grammatical aid to the knowledge of ancient Greek dialectology. Secondly, we try to show that it is possible to establish reliability criteria for the scholia, even in the presence of errors between them. The results showed that the scholia on the Acharnians present in the codex Ravennas are less reliable in the spelling. Already the scholia on the Acharnians that are in the Suda and in the codices ΕΓ are less reliable with respect to the citations. In general, the scholia from Aldina are the least reliable. In addition to these objectives and results, the present dissertation also contains a Greek compilation of the scholia on the Acharnians and an unpublished Portuguese translation of these same scholia. The compilation was made from the editions of Bekker (1829), Dindorf (1838), Dübner (1855), Martin (1882) and Rutherford (1896). In relation to epistemology, this research belongs to the field of Philology, strictly, to that of Classical Philology, with a fulcrum in Greek Philology.